Reaction rate of Na-based titanium nanofluid with water. Issue 6 (2nd June 2016) - Park, Gunyeop; Kim, Soo Jae; Park, Hyun Sun; Kim, Moo Hwan; Baek, Jehyun
Abstract : Suppression of chemical reactivity in reaction between sodium (Na) and water by Na-based titanium nanofluid (NaTiNF) was verified by measuring the difference between the H2 generation rates of NaTiNF–water reaction and sodium–water reaction (SWR). H2 generation at the beginning of the reaction was slower in NaTiNF–water reaction than in SWR. To determine the effect of temperature on the reaction rate, NaTiNF–water reactions were conducted at 104 °C, 120 °C and 150 °C. At 104 °C, the reaction rate of SWR was twice as fast as NaTiNF–water reaction. This result demonstrates that the chemical reactivity of liquid Na is suppressed by the presence of Ti nanoparticles in liquid Na. The reaction rate of NaTiNF–water reaction increased with reaction temperature. The activation energy of NaTiNF–water reaction was obtained using the Arrhenius equation.